2022
DOI: 10.1681/asn.2021050668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 3-Year Lifestyle Intervention in Patients with Chronic Kidney Disease: A Randomized Clinical Trial

Abstract: Background Supervised lifestyle interventions have the potential to significantly improve physical activity and fitness in patients with chronic kidney disease (CKD). Methods To assess the efficacy of a lifestyle intervention in patients with CKD to improve cardiorespiratory fitness and exercise capacity over 36 months, we conducted a randomized clinical trial, enrolling 160 patients with stage 3-4 CKD, with 81 randomized to usual care and 79 to 3-year lifestyle intervention. The lifestyle intervention compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 55 publications
0
32
0
1
Order By: Relevance
“…Although hemodialysis is a widespread and well-established treatment to prolong patient survival, the reduction of aerobic capacity, imbalance of the body ( 2 ), muscle mass ( 3 ), and exercise endurance lead to a lack of physical activity in patients, resulting in decreased quality of life and mobility ( 4 , 5 ). Evidence suggests that peak oxygen uptake (VO 2 Peak) during cardiopulmonary exercise testing decreases significantly in patients with kidney disease as the disease progresses and that the causes of impaired cardiopulmonary function are diverse and include anemia ( 6 , 7 ), neuropathy ( 8 ), and cardiac and vascular dysfunction ( 9 ). Therefore, the objective of hemodialysis has shifted from maintaining the basic survival and prolonging the lives of patients to improving the quality of life and promoting patients' return to society ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although hemodialysis is a widespread and well-established treatment to prolong patient survival, the reduction of aerobic capacity, imbalance of the body ( 2 ), muscle mass ( 3 ), and exercise endurance lead to a lack of physical activity in patients, resulting in decreased quality of life and mobility ( 4 , 5 ). Evidence suggests that peak oxygen uptake (VO 2 Peak) during cardiopulmonary exercise testing decreases significantly in patients with kidney disease as the disease progresses and that the causes of impaired cardiopulmonary function are diverse and include anemia ( 6 , 7 ), neuropathy ( 8 ), and cardiac and vascular dysfunction ( 9 ). Therefore, the objective of hemodialysis has shifted from maintaining the basic survival and prolonging the lives of patients to improving the quality of life and promoting patients' return to society ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, exercise-induced improvements in V̇O 2 peak are largely driven by cardiac remodelling resulting in improved stroke volume via increased in end-diastolic volume [ 42 ], which may be blunted in people with long-term chronic disease [ 43 , 44 ]. Training-induced improvements in exercise capacity and not cardiorespiratory fitness have also been observed in related populations including people with chronic kidney disease [ 45 ] and in T2DM [ 46 ]. Importantly, data supporting the potent benefit of cardiorespiratory fitness on cardiovascular disease-related and all-cause mortality are predominantly drawn from assessment of exercise capacity (time-on-test, which is then used to estimate V̇O 2 max) [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Greater health and technology literacy [58] may also support the use of DHIs to support self-management [145]. Self-management abilities may also be made more challenging in this group by high levels of depression and emotional distress as well as physical and cognitive impairments [142,146,147]. Therefore, disadvantaged groups may require additional support to ensure they achieve the best possible outcomes.…”
Section: Considerationsmentioning
confidence: 99%
“…Evidence for the effectiveness of combined interventions in the general older population appears to be inconclusive, although exercise seems be a key component [70,94,111]. Beetham et al [147] recently demonstrated the benefits of a multi-component lifestyle intervention, which also included an exercise component, for people with CKD. There are three ongoing studies utilising exercise programmes in conjunction with nutrition and psychological components that will provide further evidence for the frail CKD population [51,98,112].…”
Section: Considerationsmentioning
confidence: 99%